2016
DOI: 10.1111/gtc.12373
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63α controls YB‐1 protein stability: evidence on YB‐1 as a new player in keratinocyte differentiation

Abstract: Y-box binding protein 1 (YBX-1 or YB-1) is an oncoprotein that promotes replicative immortality, tumor cell invasion and metastasis. The increase in the abundance of YB-1 in the cell or YB-1 translocation from the cytoplasm to the nucleus is characteristic of malignant cell growth. We have previously reported that DNp63a, a transcription factor that is known to play a pivotal role in keratinocyte proliferation and differentiation, promotes YB-1 nuclear accumulation. Here, we show that YB-1 is highly expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Consistent with previous studies where multiple YB-1 immunoreactive bands were associated with complex post translational modifications [27, 31, 33], we also observed differences in the number and molecular weight of immunoreactive bands depending on the antibody used (ranging between 45 and 60 kDa). In addition, the oscillation of nuclear YB-1 expression persisted under constant conditions (constant darkness, DD) showing a circadian clock regulation rather than simply a light-dependent YB-1 rhythmicity (Figure 2C and Supplementary Figure S2D and Supplementary Table S1).…”
Section: Resultssupporting
confidence: 91%
“…Consistent with previous studies where multiple YB-1 immunoreactive bands were associated with complex post translational modifications [27, 31, 33], we also observed differences in the number and molecular weight of immunoreactive bands depending on the antibody used (ranging between 45 and 60 kDa). In addition, the oscillation of nuclear YB-1 expression persisted under constant conditions (constant darkness, DD) showing a circadian clock regulation rather than simply a light-dependent YB-1 rhythmicity (Figure 2C and Supplementary Figure S2D and Supplementary Table S1).…”
Section: Resultssupporting
confidence: 91%
“…It is documented that the functions played by YB-1 are strictly dependent on its subcellular localization [ 16 , 39 , 40 ]. Thus, we examined YB-1 subcellular localization in human HEK293T cells in resting conditions and following treatment with Na Ars, a well-known inducer of oxidative stress and translational arrest [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that intracellular YB-1 is implicated in keratinocytes proliferation and survival to oxidative stress [ 40 , 48 ]. To get an insight into the function of secreted YB-1 we evaluated the proliferative response of HaCaT cells to the addition of rYB-1 or HPLC-purified YB-1 from HEK293T cell culture medium (CCM-YB-1).…”
Section: Resultsmentioning
confidence: 99%
“…YB-1 can also be secreted [ 88 ]. Acetylation and ubiquitination of YB-1 have both been shown to play roles in regulating secretion as well as intracellular stability [ 58 , 90 , 107 , 108 ]. YB-1 can be proteolytically cleaved and extracellular YB-1, and/or fragments thereof, is found in the serum of patients, binds to cell surface receptors, and exerts extracellular activities, e.g.…”
Section: Cold Shock Proteins In Diseasementioning
confidence: 99%